The Role Of Sharia Economic Law In Supporting A Healthy Economic System For Indonesian Communities - Hasan, Zahid; Nurhuda, Abid (Universitas Islam Negeri Raden Intan Lampung, 2023)
The dynamics of the development of Sharia economic law in Indonesia have developed rapidly so that in the management of the economy, Sharia and conventional banking have emerged. The lower middle class and informal workers are very vulnerable to being trapped in conventional banks, causing pain in the Indonesian economy. So the purpose of this research is to describe the Role of Sharia Economic Law in Supporting a Healthy Economic System for Indonesian Society. The method used is literature study, then the data is collected using a qualitative approach, then the truth and validity are analyzed and the last is concluded descriptively. The results of the study show that the Role of Sharia Economic Law in Supporting a Healthy Economic System for Indonesian Communities includes making people aware of the importance of paying Zakat, supporting the Prohibition of usury, fostering expectations of economic cooperation, supporting the social security system, supporting the prohibition of business practices which is dirty, and supports the supervision of the sharia economy in the state order so that all of these roles are following the maqosidu sharia which has been established by Islamic teachings.Keywords: Role, Sharia Economic Law, Healthy Economy, Indonesian Society